2024
DOI: 10.24925/turjaf.v12i2.159-178.6452
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Apple Production in Jumla District, Nepal: Status, Economics, Marketing and Challenges

Roshan Thapa,
Sudip Ghimire,
Prakriti Bhattarai
et al.

Abstract: Apple production is a vital sector of agriculture in Nepal, significantly impacting local livelihoods and the regional economy. This study, conducted in Jumla District, Nepal, from January to July 2022, aims to comprehensively assess apple production, including its existing conditions, economic implications, marketing and challenges. The research hypothesizes that while apple production in Jumla District contributes significantly to the local economy, it faces challenges related to pest and disease management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Preliminary insights into the field conditions, socio-cultural settings, and demographic and topographic features of the study area were acquired through frequent field visits, as suggested by Ghimire and Chhetri (2023), Ghimire and Rauniyar (2023) and Thapa et al (2024). These visits informed the preparation of interview schedules, design of the sampling framework, and application of sampling techniques, facilitating efficient data collection during the subsequent household survey.…”
Section: Survey Design and Data Collection Methodsmentioning
confidence: 99%
“…Preliminary insights into the field conditions, socio-cultural settings, and demographic and topographic features of the study area were acquired through frequent field visits, as suggested by Ghimire and Chhetri (2023), Ghimire and Rauniyar (2023) and Thapa et al (2024). These visits informed the preparation of interview schedules, design of the sampling framework, and application of sampling techniques, facilitating efficient data collection during the subsequent household survey.…”
Section: Survey Design and Data Collection Methodsmentioning
confidence: 99%
“…Apple production is a main source of income in the Jumla district of Nepal, playing a crucial role in food security (Atreya and Kafle, 2016). The climatic condition of the district, marked by high altitude, low humidity, and plenty of sunshine creates a favorable condition for apple cultivation (Thapa et al, 2024) and due to less precipitation and ample cold days, the growing season for crops are shorter (Krap, 2012). Farming Apple proves to be a gift to the farmers of the Jumla district because of its economic, social, and environmental benefits (Subedi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%